Chapter 3 'Ordering the infant' caring for newborns in early modern England - Astbury, Leah (Social Histories of Medicine, 2017)
This chapter focuses on the specific forms of health care given to newborn babies in early modern England, a hitherto almost entirely neglected category in histories of health. Drawing on printed health advice and correspondence the chapter charts the various stages of the care offered to newborns, which was based on very specific management of the six non-naturals appropriate to their uniquely hot, damp constitutions, and fragile, malleable bodies. This care was determined particularly by attentive observation and physical 'searching' of the body. It was crucial to ensure first that all forms of 'excretion' were possible: whether via the mouth or the anal passage; whether excreting excessive moisture from the throat, stomach and brain through crying or removing excrements from the skin through wiping and bathing. Gentle forms of exercise were necessary and procured through crying, bathing or gentle rubbing of the skin. Excessive crying however endangered its health and carers were given advice on calming and soothing babies whilst sleep was of utmost importance, not only in terms of duration but also the baby's position whilst sleeping.